La clase de literatura: revisión bibliográfica sobre las propuestas de la enseñanza de literatura en las aulas de Colombia durante el periodo 2009-2019 (2020)
Through this compilation work, a bibliographic review is made around the different pedagogical proposals that have been carried out in public and private educational institutions between 2009 and 2019 in Colombia. Through a process of categorization and analysis, it was sought to identify which are the teaching practices of literature that are being presented in the classrooms to determine the most representative trends in the country.